Réponses

Meilleure réponse !
2014-09-11T22:05:57+02:00
Exercice 22 :

O(x) = (4x + 3)² - 2(4x + 3) (x + 2)
        = (4x + 3) (4x + 3 - 2x -4)
        = (4x + 3) (2x -1)

P(x) = 4x² + 4x + 1 + (2x + 1) (x - 2)
        = (2x + 1)² + (2x + 1) (x - 2)
        = (2x + 1) (2x + 1 + x - 2)
        = (2x + 1) (3x -1)

Q(x) = 49 - (x + 2)²
        = (7 - x - 2) (7 + x + 2)
        = (5 - x) (9 + x)

R(x) = x² - 25 + 2(x - 5) (x + 3)
        = (x - 5) (x + 5) + 2(x - 5) (x + 3)
        = (x - 5) (x + 5 + 2x + 6)
        = (x - 5) (3x + 11)